Handbook of physics - Benenson, Walter; Gale Group (New York, N.Y. Springer, 2002)
Provides access to information including not only the fundamental formulas of physics but also a wide variety of experimental methods used in practice. Provides information for everyday use in problem solving, homework, examinations, and practical applications of physics.
Preface -- Contributors -- Part I. Mechanics -- Part II. Vibrations and Waves -- Part III. Electricity -- Part IV. Thermodynamics -- Part V. Quantum physics -- Part VI. Appendix -- 33 Tables on the SI -- Index -- Natural constants in SI units -- Thermodynamic formulas -- Periodic table.
Electronic reproduction.
Keywords: Physics -- Handbooks, manuals, etc; Physics -- Methodology -- Handbooks, manuals, etc; Electronic books